Effect of TiC on the impact abrasive wear resistance of low alloy martensitic steel. (November 2022) - Zhang, Peng; Qiu, Han; Cao, Lin; Tu, Xiaohui; Cui, Jie; Yu, Helong; Li, Jie; Wang, Qiwei; Yang, Junjie; Li, Wei; Lin, Huaijun
Abstract: The effect of TiC on the impact abrasive wear (IAW) resistance of low alloy martensitic steel was investigated by comparing the abrasive wear (AW) and IAW behaviours of JFE400 (without carbides) and Ti60 (with 3.25 % TiC). Under AW conditions, weight loss is mainly caused by abrasive wear. Under IAW condition, fatigue cracks are formed at the interface of deformed layer (DL) / matrix in the worn subsurface. Abrasive and delamination wear are responsible for weight loss. In addition to weaken the abrasive microploughing, TiC can also inhibit the formation of DL composed of nanosized grains by dynamic recrystallisation, thereby preventing fatigue crack propagation. Therefore, the relative wear resistance of Ti60/JFE400 increased from 1.38 (AW) to 1.60 (IAW). Highlights: The abrasive wear (AW) loss is caused by abrasive microploughing. The impact AW (IAW) loss is caused by abrasive microploughing and crack. The relative wear resistance of Ti60/JFE400 increases from 1.38 (AW) to 1.60 (IAW). The abrasive microploughing and crack propagation is inhibited by TiC. TiC reduces the cracks by suppressing the formation of deformed layers.